The Impact of Zakat Utilization and Business Financing on Welfare with Business Sustainability as a Moderating Variable (Case Study of BAZNAS Labuhanbatu Utara) - Fadillah Ramadhani Siregar; Muhammad Syahbudi; Muhammad Lathief Ilhamy Nasution (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2024)
This article aims to examine the impact of zakat utilization and business financing on the welfare of beneficiaries (mustahik), with business sustainability as a moderating variable. A case study was conducted at BAZNAS Labuhanbatu Utara. The research method employed a quantitative approach, utilizing questionnaires distributed to 100 mustahik who have received zakat in the form of business capital and participated in economic empowerment programs from 2023 to 2024. Data analysis was conducted using path analysis.The results indicate that zakat utilization has a significant positive impact on the welfare of mustahik. Additionally, business sustainability plays a crucial role as a moderating variable that strengthens the influence of zakat on mustahik welfare. This research underscores the importance of zakat management oriented towards business sustainability to enhance the long-term impact on the welfare of mustahik. Furthermore, it aligns with Islamic economic law, which emphasizes the ethical distribution of wealth and resources to ensure social justice and promote community welfare, reflecting the broader objectives of Maqasid al-Shariah in fostering economic development and reducing poverty.